Eltrombopag use in a patient with Wiskott–Aldrich syndrome. Issue 12 (23rd June 2017) - Gabelli, Maria; Marzollo, Antonio; Notarangelo, Lucia Dora; Basso, Giuseppe; Putti, Maria Caterina
Abstract: Wiskott–Aldrich syndrome (WAS) is an inherited X‐linked disorder characterized by microthrombocytopenia, immunodeficiency, and eczema. Hematopoietic stem cell transplantation (HSCT) is the treatment of choice. Eltrombopag, a thrombopoietin receptor agonist, may be useful to prevent bleeding while awaiting HSCT. We present a case of a male with WAS, profound thrombocytopenia, and bleeding diathesis successfully managed with eltrombopag before HSCT. Eltrombopag was given for 32 weeks obtaining a stable platelet count without any platelet transfusion. The patient did not experience any bleeding symptom. Eltrombopag may be a suitable therapeutic option for patients with WAS and severe thrombocytopenia as "bridge" to definitive cure.